Drifters, Drogues, and Circulation - Thomas O. Manley (Oceanography, 2010)
Circulation within a body of water controls not only fluid transport, but just as importantly, chemical, biological, and sedimentological constituents. Transport and dispersal of these constituents is of major concern when it comes to the proper management of rivers, bays, lakes, and nearshore communities, however, most students fail to realize the complexities related to the forcing of this flow field or its variability over time. Through the use of very basic tools, students having access to a small research vessel would be able to map surface and deeper circulation of a small region within a given water body (for ease, “lake” will be used from here on even though it implies any region of interest). Meteorological data will be used to look at the effects of wind forcing while bathymetric information can provide aspects of topographic control. The acquisition of these data during repeated cruises will lead to a better understanding of mean circulation and its variability.